We scrape together pennies: fairness and effectiveness of monetary sanctions - Ruhland, Ebony L. (Journal of crime and justice, 2024)
Monetary sanctions are in every part of the criminal legal system. This paper explores monetary sanctions in community supervision (probation and parole). The findings from a mixed-methods, multiple-state research study illustrate how fines and fees are administered, collected, and enforced within community supervision. Supervision officers have little discretion in the number of fines and fees assessed but have more discretion in collecting the payments and punishing or sanctioning nonpayment. The findings in this paper also elucidate how individuals and their social supports experience having to pay monetary sanctions. The burden of financial sanctions is not felt only by the individual on supervision but also extends to the family. The article concludes with recommendations for improving the use of monetary sanctions within community supervision.